2009
DOI: 10.1093/schbul/sbp092
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Impaired Sound Intensity Processing in Schizophrenia

Abstract: Patients with schizophrenia are impaired in many aspects of auditory processing, but indirect evidence suggests that intensity perception is intact. However, because the extraction of meaning from dynamic intensity relies on structures that appear to be altered in schizophrenia, we hypothesized that the perception of auditory looming is impaired as well. Twenty inpatients with schizophrenia and 20 control participants, matched for age, gender, and education, gave intensity ratings of rising (looming) and falli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Interview measures of perceptual abnormalities, as distinct from hallucinations, indicate that auditory distortions are more frequent than distortions in any other sensory modality, occurring in 42% of patients with SZ compared to 17% of healthy adults (Bunney et al, 1999). Consistent with these subjective reports, behavioral measures of auditory processing have demonstrated deficits in time estimation (Carroll et al, 2009), spatial localization (Perrin et al, 2010), sound intensity discrimination (Bach et al, 2011) pitch discrimination (Leitman et al, 2008) and echoic memory (Strous et al, 1995). Event-related potential (ERP) findings suggest that auditory processing is affected within 50–200 ms of stimulus onset, including reduction of the P50 response to the first click of a paired click paradigm, impaired P50 gating, reduction of the auditory N100 component, and reduced mismatch negativity (see Hirayasu et al, 1998; Turetsky et al, 2007).…”
Section: 1 Introductionmentioning
confidence: 83%
“…Interview measures of perceptual abnormalities, as distinct from hallucinations, indicate that auditory distortions are more frequent than distortions in any other sensory modality, occurring in 42% of patients with SZ compared to 17% of healthy adults (Bunney et al, 1999). Consistent with these subjective reports, behavioral measures of auditory processing have demonstrated deficits in time estimation (Carroll et al, 2009), spatial localization (Perrin et al, 2010), sound intensity discrimination (Bach et al, 2011) pitch discrimination (Leitman et al, 2008) and echoic memory (Strous et al, 1995). Event-related potential (ERP) findings suggest that auditory processing is affected within 50–200 ms of stimulus onset, including reduction of the P50 response to the first click of a paired click paradigm, impaired P50 gating, reduction of the auditory N100 component, and reduced mismatch negativity (see Hirayasu et al, 1998; Turetsky et al, 2007).…”
Section: 1 Introductionmentioning
confidence: 83%
“…If auditory deficits in SZ are primarily due to poor encoding of frequency or pitch, sound segregation on the basis of other cues might offer opportunities for those with SZ to take advantage of redundant cues in the environment to discriminate separate sound sources. However, previous behavioral evidence showed that people with SZ have deficits in processing other acoustic cues such as intensity, duration, and spatial location (Bach et al, 2011; Davalos et al, 2003; Elvevag et al, 2003; Penney et al, 2005; Perrin et al, 2010). Additionally, electrophysiological evidence has shown reduced cortical responses of the mismatch negativity (MMN) response in Sz (Michie, 2001); the MMN is elicited when deviant changes in stimulus characteristics are detected within a backdrop of repeated standard sounds.…”
Section: Introductionmentioning
confidence: 96%
“…Family, premorbid and first-episode studies would be useful in clarifying when the musical deficits can be first observed and to what extent the deficits increase during the course of the illness. Acoustic studies of patients with schizophrenia have demonstrated impaired processing of sound intensity changes, 29 and difficulties in extracting emotional meaning from prosody. 41,42 Verbal prosodic pitch discrimination has also been reported to be impaired and to correlate with positive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Dysfunction of auditory information processing and altered perception of pitch and intensity are also observed. 29 Abnormalities in detection of the prosodic qualities of speech in patients with schizophrenia are linked to auditory pathways. 30 The negative symptoms of schizophrenia are also associated with abnormalities in detecting frequency modulated tones designed to mimic key acoustic features of human vocal expressions.…”
Section: Introductionmentioning
confidence: 99%